Arabic Language Curriculum Design Based on Higher Order Thinking Skills (HOTS) in Islamic Educational Institutions - Ilham Kholiq (Funun Arabiyyah: Journal of Arabic Education and Literature, 2026)
This study aims to analyze and conceptualize an integrative Higher Order Thinking Skills (HOTS)-based Arabic language curriculum design in Islamic educational institutions. The novelty of this study lies in its integrative framework that combines instructional design models, HOTS pedagogy, and Islamic epistemological perspectives. This research employs a qualitative literature review method by analyzing curriculum policy documents and relevant scientific literature. The data were selected based on relevance, recency, and contribution to HOTS-based curriculum development. The findings reveal a significant gap between curriculum policy and classroom implementation, particularly in teaching materials and assessment practices that remain dominated by LOTS. This study proposes an integrative curriculum model connecting objectives, materials, strategies, and assessment. Theoretically, this study contributes to the development of HOTS-based curriculum design within Islamic education. Practically, it offers a framework for educators and policymakers. However, this study is limited to literature-based analysis and does not include empirical field validation